Accuracy of Intraoperative Determination of Central Node Metastasis by the Surgeon in Papillary Thyroid Carcinoma. (April 2014) - Ji, Yong Bae; Lee, Dong Won; Song, Chang Myeon; Kim, Kyung Rae; Park, Chul Won; Tae, Kyung
Objective: Prophylactic central neck dissection (CND) in papillary thyroid carcinoma (PTC) remains controversial. If the presence of central lymph node metastasis could be assessed preoperatively or intraoperatively, unnecessary CND could be avoided. The aim of this study was to evaluate the accuracy of intraoperative determination of central lymph node metastasis by the surgeon using palpation and inspection in clinically node-negative PTC. Study Design: Prospective study. Setting: University tertiary care facility. Subjects and Methods: A total of 122 consecutive patients with clinically node-negative PTC were enrolled. Any suspicious lymph nodes on intraoperative palpation or inspection were sent for frozen biopsy, and then bilateral CND with total thyroidectomy was carried out in all patients. The criteria for a suspicious lymph node included palpable hardness, dark discoloration, or size exceeding 5 mm in diameter. We compared the surgeon's judgments with the final pathologic results. Results: Suspicious lymph nodes were found in 37 (30.3%) patients, and 15 of them had metastasis on permanent biopsy. Of 85 patients with no suspicious lymph nodes, 27 (31.8%) had metastasis on permanent biopsy. The sensitivity and specificity as well as positive and negative predictive values of intraoperative determination of central lymph node metastasis were 35.7%, 72.5%, 40.5%, and 68.2%, respectively. The positive predictive values of enlarged lymph nodes, dark discoloration, and hardness were 30.4%, 50.0%, and 78.6%, respectively. Conclusion: Intraoperative determination of central lymph node metastasis by the surgeon is a limited guide for CND in clinically node-negative PTC because of its low sensitivity and specificity.